2016
DOI: 10.1515/amsc-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Coal Loading by Cutting Drum in Flat Seams

Abstract: This paper presents a methodology for modeling work of a coal shearer work in low longwall coal seams where the wall height does not exceed 1.5 m. In such conditions, an important issue is the process of loading the ore from shearer cutting drum on an armored face conveyor and selection of appropriate kinematic parameters to avoid choking. Discrete element method was used to model coal seam. This method allows for efficient simulation of physical systems composed of many separate components. Methods and algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…With the improvement of computer performance and numerical analysis software, the numerical model has dominated in coal cutting research with lower cost and higher efficiency [14]. In addition, the accuracy of results obtained from the simulation method has been verified in a previous study [15]. Pijush Samui [16] studied the cutting performance under different cutting tools, cutting angles, cutting depths, and velocities with the finite element method, and the results showed that these mentioned parameters affect the cutting efficiency significantly.…”
Section: Introductionmentioning
confidence: 88%
“…With the improvement of computer performance and numerical analysis software, the numerical model has dominated in coal cutting research with lower cost and higher efficiency [14]. In addition, the accuracy of results obtained from the simulation method has been verified in a previous study [15]. Pijush Samui [16] studied the cutting performance under different cutting tools, cutting angles, cutting depths, and velocities with the finite element method, and the results showed that these mentioned parameters affect the cutting efficiency significantly.…”
Section: Introductionmentioning
confidence: 88%
“…The The productivity of the drum shearer was calculated with using (5). All experiments were carried out under the equal conditions of the movement of the drum shearer SL-500/1 to a certain depth into the coal seam in Ilevsky Mine in Kuznetsk Coal Basin.…”
Section: The Simulation Modelmentioning
confidence: 99%
“…Li Wei [14] proposed a hidden Markov model (HMM) memory cutting method for the shearer, which prevented large residual errors and frequent adjustments of the shearer cutting drum. Gospodarczyk Piotr [15] focused on the coal mining process for different variants of the shearer construction and kinematic parameters. Xu Jing [16] proposed an online cutting-pattern recognition method with high accuracy and speed.…”
Section: Introductionmentioning
confidence: 99%